THE CORRELATION BETWEEN STUDENTS' MOTIVATION IN READING FICTION STORY AND THEIR ABILITY TO WRITING NARRATIVE PARAGRAPH - Nurul Fhadilah Rauf; Ummi Khaerati Syam; St.Asmayanti Amaliah (FKIP Unismuh Makassar, 2022)
The objective of the research was intended to identify the students’ interest in writing narrative paragraph, their ability in writing narrative paragraph and knowing whether or not there was a correlation between students’ interest and their ability of student’s class XI at MA Al-hidayah Makassar. This research Proposal will find out the correlation between students' motivation in reading fiction story and their ability to writing narrative paragraphs that focuses on students’ motivation in reading fiction story and their ability to writing narrative paragraphs. Special for writing ability, namely writing narrative paragraphs, focused, and concerned with the paragraph content and vocabulary. The writer will apply pre-experimental method with questioner and writing test, and collect the data based on the test. The sample of the research will choose class XI at MA Al-hidayah Makassar. The sample will take by using purposive sampling technique. The result of the data indicated that the mean score of the students’ motivation in reading fiction story is 75.36 and it is classified as high motivation and the minimum score is 69.00, and the maximum score is 79.00. Next, the mean score students’ writing narrative paragraphs is 72.12 and it is classified as fair category, the minimum score is 61, and the maximum score is 79.